(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the interface and interphase structure between matrix and reinforcing fibers in fiber-reinforced polymer (FRP) composites, their influence on mechanical properties and load transfer mechanisms. Interface degradation, microcrack formation, and environmental effects are discussed. Theoretical models and experimental methods are also reviewed.